2018
DOI: 10.23876/j.krcp.18.0080
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a novel predictor of preterm labor in severe preeclampsia

Abstract: BackgroundThe most common cause of acute kidney injury (AKI) in pregnancy is preeclampsia. Serum cystatin C (CysC) is a potential biomarker of early kidney damage as its levels are not disturbed by volume status changes in pregnancy, and serum CysC levels could serve as a replacement for conventionally used creatinine. In this study, we investigated the serum levels of CysC in severe preeclampsia cases and the associations between CysC levels and poor obstetric outcomes.MethodsOur cohort included severe preecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
3
13
1
Order By: Relevance
“…In the present study, interestingly, Wattanavaekin et al [6] suggested an additional relevant role for cystatin C in women with preeclampsia independent of renal function. Even among women with preeclampsia, elevated cystatin C levels may predict adverse pregnancy outcomes, such as preterm birth.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…In the present study, interestingly, Wattanavaekin et al [6] suggested an additional relevant role for cystatin C in women with preeclampsia independent of renal function. Even among women with preeclampsia, elevated cystatin C levels may predict adverse pregnancy outcomes, such as preterm birth.…”
supporting
confidence: 64%
“…In this issue of Kidney Research and Clinical Practice , Wattanavaekin et al [6] explored the role of cystatin C in a prospective cohort of 26 women with preeclampsia, all with a normal kidney function with serum creatinine 0.4 to 0.8 mg/dL. The authors found a marked difference between cystatin C-based and creatinine-based eGFR values.…”
mentioning
confidence: 99%
“…Hemodynamic adaptations are essential during pregnancy to ensure adequate circulation to the placenta and to meet the increased metabolic demands of the developing fetus, and include remodeling of cardiac tissue, increases in blood volume, increased cardiac output, and vasodilation of the vasculature and kidneys [40,41]. Higher levels of cystatin C are associated with risk for preeclampsia diagnosis [42][43][44][45], a cardio-metabolic disease of pregnancy driven by distress signals released by an ischemic placenta. Preeclampsia is also associated with risk for shorter gestational length and low birthweight [46].…”
Section: Discussionmentioning
confidence: 99%
“…Cysc, the alternative test of Cre used in glomerular ltration rate estimation, was found elevated in PE patients (31) and was able to predict PE in combination of neutrophil gelatinase-associated lipocalin (AUC = 0.88) (32). Moreover, Cysc was reported as a predictor of preterm labor in severe PE, although the physiological increase of Cysc during pregnancy may pose an additional confounding factor in its clinical evaluation (33). In a prospective study with relatively large cohort (n = 9522) by Rezk et al, the serum UA was found to be a useful PE predictor for women at moderate or low risk (34).…”
Section: Discussionmentioning
confidence: 99%